WERNICKE–KORSAKOFF SYNDROME, SUBSTANCE USE AND ABUSE: NEUROPSYCHOLOGICAL AND PSYCHOMOTOR EFFECTS. (Fiep Bulletin - online, 2014)
The use and abuse of chemical substances can change different cognitive, emotional and motor functions in human beings (as perception, behavior, motor skills, judgment, attention, and memory), reflecting in a social, economic, biological and psychological way in the drug user's life and his or her family. Chemical dependency is a public health problem and needs health promotion policies. OBJECTIVE: To investigate neuropsychological and psychomotor aspects of an individual diagnosed with Wernicke-Korsakoff syndrome and history of substance use and abuse (alcohol, cocaine and crack).METHODOLOGY: Descriptive research, type of study regarding clinical case on Syndrome of Wernicke-Korsakoff, substance use and abuse. CONCLUSION: Wernicke-Korsakoff Syndrome affects the Central and Peripheral Nervous System, presenting symptoms as damage in memory and learning abilities, mental confusion, ophthalmoplegia, ataxia and mental disorders, in addition to injuries of the brain structures, more frequently found in chronic alcoholics (especially those presenting low levels of thiamine). Need of treatment using multidisciplinary approach directed to the patient and his or her family.
Keywords: Neuropsychology; Psychomotricity; Wernicke-Korsakoff Syndrome.